First-Generation Highly Skilled Migrants from a South-Asian Country (Glocalism: Journal of Culture, Politics and Innovation, 2022)
This paper presents findings of a study that investigated causes for migration, the expectations of migration and post-migration experience of IT professionals from Sri Lanka. The paper also discusses effects of education qualification from abroad, past work experience from abroad, and homeownership before migration on skilled migration. For the study, survey methodology was used, and two different sample groups were selected – migrants and prospective migrants from the IT sector. The results indicated two domains of causes and four domains of expectations. There were significant differences between  expectations and post-migration experience of migrants; there were significant differences in some causes for migration and expectations and postmigration experience by homeownership before migration. The paper concludes with a discussion on implications of the findings for theory and practice.
Keywords: highly skilled migrants; international migration; migrant; post-migration experience; prospective migrant